Teaching learning strategies in the Early Years of Elementary School: an exploratory analysis (Research, Society and Development, 2022)
Learning strategies consist of a set of procedures used by students to learn. The teaching of learning strategies in the educational context can favor student learning and performance. Therefore, this research aimed to analyze the conceptions of learning strategies of teachers of the early years of elementary education and to identify which learning strategies are taught by them in the school context. Eight teachers from a public school located in the interior of the state of Paraná participated in the study. The teachers answered a sociodemographic questionnaire and a questionnaire investigating the teaching of learning strategies. The questionnaires were designed especially for this research. The questionnaires were sent using Google Forms tools. The data were analyzed using the Content Analysis proposed by Bardin (2016). The results revealed that although teachers reported knowing what learning strategies are, most confuse them with teaching strategies. Among the learning strategies reported by teachers, cognitive strategies are the most mentioned, followed by metacognitive strategies and social self-regulation strategies. It is considered important to use and teach learning strategies regardless of the level of education in which the students are and that they be taught in initial and continuing education courses for teachers, so that they become promoters of learning strategies in the school environments in which they work.